Relations of the Conference of the Episcopate of Poland with the authorities of the Polish People Republic in the years 1980-1981 - Stępień, Marek (Prawo Kanoniczne, 2020)
After the Second World War communists took over the power in Poland. The main purpose of the ruling party was introducing the principles of Marxist philosophy. In the center of ideological fight was the Roman Catholic Church perceived as serious obstacle or even threat in achieving their goals. In the years 1980-1981, the Polish authorities again declared their will to normalize relations and to reactivate the Joint Commission of the Government and the Episcopate. The communists as the rulers counted on the help of the Church in calming social moods and normalizing the situation after the unrest and strikes that took place at that time. The talks however did not bring any significant effects. Only a few small matters were settled.